Investigation of the preservice teachers' science-pseudoscience distinction and epistemological beliefs - Nagihan Tanık Önal; Aslı Saylan Kırmızıgül (Journal of Pedagogical Research, 2021)
This study aims to investigate preservice teachers' science-pseudoscience distinctions, epistemological beliefs, and to explore the relationship between these two parameters. To this end, a correlational research design has been employed. The study was conducted with the participation of 182 preservice science and preschool teachers, with the data being collected through the Science-Pseudoscience Distinction Scale and Epistemological Beliefs Questionnaire using descriptive statistics, multiple regression analyses, and correlation analyses. The results reveal the participants to have sophisticated epistemological beliefs and the ability to distinguish between science and pseudoscience, as well as a positive medium-level correlation between these two variables. Moreover, when comparing results through the variables of gender, department, and whether or not teachers follow scientific publications or broadcasts, these variables have been found to not predict participants' levels of science-pseudoscience distinction or epistemological beliefs. The preservice teachers' levels of science-pseudoscience distinction were found to vary significantly only based on grade level and favoring of senior preservice teachers. In more specific analyses, the preservice science teachers' epistemological beliefs were found to be more developed than preservice preschool teachers, with epistemological beliefs to be more developed as grade level increases. In light of these findings, lessons are recommended to be enhanced with activities designed to improve epistemological beliefs and the ability to distinguish between science and pseudoscience.